The effectiveness of Online Process Writing Portofolio Program to Improve the Writing Ability of S1 English Department Students Faculty of Teacher Training And Education â UT at Yogyakarta Distance Learning Program Unit - Sudilah, Sudilah (Universitas Ahmad Dahlan, 2015)
This paper is written based on the findings of an Action Based Research aimed at knowing whether the implementation of an online Process Writing Portfolio Program (PWPP) is effective in improving the long distance studentsâ writing ability. The subjects of the study are the students of Faculty of Education and Teacher Training, Universitas Terbuka, at Yogyakarta Long Distance Learning Program Unit. The data are collected from three cycles of the program implementation via email : sudilah@ut.ac.id. Each cycle consists of 4 stages, the plan, action, observation, and reflection. Grades of each cycle were taken from 4 kinds of activities; brainstorming, first draft writing, revising and editing, and final copy. The score increase from cycle to cycle is used to measure the improvement of the studentsâ writing ability. For this purpose the writer uses Wilcoxson Signed Ranks Test and Scoring Scale for Composition. The results of the study indicate that the implementation of online Process Writing Portfolio Program is merely effective in improving the studentsâ writing ability in terms of numerical grade scores. From the Pre- Program Implementation (Pre- PI) to Cycle I, the average increase of the studentsâ writing score is 6.51. After the implementation, that is from the (Pre-IP) cycle to cycle I, the increase achieved is Z =.380 and p = .017 (p <0.05), and from cycle I to II is) Z = 2524 with p = .012 (p <0.05), and from cycle II to III the improvement increase is Z = 2524 with p = .012 (p <.0.05). It means that all of the increase is significant. Yet, if the scores are converted to Skidmoreâs criteria of Scoring Scale for Composition, the quality of the paragraphs does not increase significantly. All of the paragraphs are not publishable yet. Many aspects of refinement are still needed to display or publish the paragraph. Keywords: effectiveness, to improve, online Process Writing Portfolio ProgramÂ